Criteria of Acts that Can be Classified as Religious Blasphemy - Yanto, Oksidelfa (al-'adalah, 2021)
This study discusses the criteria for actions that can be classified as acts of religious blasphemy. The aim is to find out in-depth the types of actions that can be classified as criminal acts of blasphemy, as well as legal provisions and sanctions against perpetrators who intentionally commit such acts. This research is descriptive qualitative using a normative juridical approach. To obtain data in viewing the issues discussed, the authors use normative juridical research methods through library research using secondary data. The results of the study show that the acts of religious blasphemy include all kinds of slanderous actions aimed directly at the religion professed, either orally or in writing, regardless of whether it will endanger public order or not, with the aim that people do not adhere to a particular religion. In the realm of criminal law, the case of blasphemy is a form of a pure criminal event whose perpetrators can be given legal sanctions. The legal sanctions for perpetrators according to the Criminal Code can be sentenced to 5 (five) years in prison